Poincaré plot indexes of heart rate variability: Relationships with other nonlinear variables - Hoshi, Rosangela Akemi; Pastre, Carlos Marcelo [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP]; Godoy, Moacir Fernandes (My University, 2013)
The Poincaré plot for heart rate variability analysis is a technique considered geometrical and non-linear, that can be used to assess the dynamics of heart rate variability by a representation of the values of each pair of R-R intervals into a simplified phase space that describes the system's evolution. The aim of the present study was to verify if there is some correlation between SD1, SD2 and SD1/SD2 ratio and heart rate variability nonlinear indexes either in disease or healthy conditions. 114 patients with arterial coronary disease and 65 healthy subjects underwent 30. minute heart rate registration, in supine position and the analyzed indexes were as follows: SD1, SD2, SD1/SD2, Sample Entropy, Lyapunov Exponent, Hurst Exponent, Correlation Dimension, Detrended Fluctuation Analysis, SDNN, RMSSD, LF, HF and LF/HF ratio. Correlation coefficients between SD1, SD2 and SD1/SD2 indexes and the other variables were tested by the Spearman rank correlation test and a regression analysis. We verified high correlation between SD1/SD2 index and HE and DFA (α1) in both groups, suggesting that this ratio can be used as a surrogate variable. © 2013 Elsevier B.V.
Keywords: Chaos theory; DFA (α1); Heart rate variability; Nonlinear analysis; Poincaré plot; adult; comparative study; coronary artery disease; correlation coefficient; female; heart index; heart rate variability; human; major clinical study; male; nonlinear system; poincare plot index; priority journal; regression analysis; RR interval; supine position